Superabsorbent Polymers as a Poultry Litter Amendment - Timmons , Jennifer R.; Harter-Dennis, Jeannine M. (International Journal of Poultry Science, 2011)
Ammonia volatilization from poultry litter commonly causes a buildup of ammonia in the atmosphere of chicken houses that can have a negative impact on both farm workers and birds. The release of ammonia from poultry houses can also contribute to environmental problems such as atmospheric haze. The most widely accepted management strategy to control ammonia volatilization from poultry houses is the use of litter amendments that are added to the litter. The poultry industry routinely uses dry acids such as aluminum sulfate and sodium bisulfate to reduce ammonia emissions inside the poultry house. Although these products are very effective in controlling ammonia release in poultry houses, they typically only work for about the first three weeks of the grow-out period, after which time litter pH and ammonia levels will begin to rise. As a result, these litter amendments must be reapplied prior to the placement of new chicks in order for ammonia levels to continually remain low. Therefore this research was conducted to evaluate the efficacy of an alternative product for long-term control of ammonia release in poultry houses. This research investigated the efficacy of a single application of superabsorbent polymers to poultry litter for long term in-house ammonia control which could reduce the negative impacts of ammonia on bird health and performance and potentially the environment.